(untitled) (Research, Society and Development, 2022)
The Cerebrovascular Accident (CVA), commonly called stroke, is characterized by the interruption of blood flow to the brain, due to the blockage or rupture of brain blood vessels. The objective of this study is to analyze the number of hospitalizations for stroke in young adults in the state of Paraíba in the period between 2017 and 2021. Method: This is a quantitative research, based on an epidemiological and retrospective study, carried out in the state of Paraíba, has an empirical, descriptive and documentary character. The data used come from the Hospital Information System (SIH), from secondary data taken from the public and national database of the system’s Health Portal entitled DATASUS, in a monthly analysis of hospitalization for stroke in young adults in the state of Paraíba , recorded from 2017 to 2021. The results presented indicate that increasing age acts as a vulnerability factor for the occurrence of stroke and that women are proportionally more affected by stroke than men. In both sexes, the most prevalent age group is between 40 and 49 years old and the lowest incidence rate is between 20 and 29 years old. It was also seen an increase in the number of hospitalizations during the years analyzed. It is concluded then that the results of this study help to understand the behavior of hospitalizations for stroke in the state of Paraíba. It is expected that the presented scenario can help in the construction of future investigations, in the decision making in face of the control of the incidence of CVA and of its strategies to face the disease prevention.